2017
DOI: 10.1136/bmjopen-2017-018270
|View full text |Cite
|
Sign up to set email alerts
|

Early interventions for the prevention of post-traumatic stress symptoms in survivors of critical illness: protocol for a systematic review

Abstract: IntroductionPost-traumatic stress disorder (PTSD) is being increasingly reported among survivors of critical illness and injury. Previous work has demonstrated that PTSD reduces patient quality of life and ability to return to work, as well as increases healthcare costs. As such, identifying interventions aimed at preventing the development of critical illness-related PTSD could have an important public health impact. The objective of this systematic review is to collate the world’s literature on early interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…However, I felt sure that our therapeutic skills could be offered in some form as acute support for key workers. I found some studies suggesting that early intervention may be able to mitigate PTSD symptoms in some staff (Glaspey et al, 2017); while the research here is drawn from a small pool, initial findings suggested a similar service could help. My colleague Jonathan Cousins-Booth alerted me to Psychological First Aid, a training his company had received (Everly, 2020) and suggested this could be a useful model to inform NLMT's Phone Support Service.…”
Section: Service Outlinementioning
confidence: 85%
“…However, I felt sure that our therapeutic skills could be offered in some form as acute support for key workers. I found some studies suggesting that early intervention may be able to mitigate PTSD symptoms in some staff (Glaspey et al, 2017); while the research here is drawn from a small pool, initial findings suggested a similar service could help. My colleague Jonathan Cousins-Booth alerted me to Psychological First Aid, a training his company had received (Everly, 2020) and suggested this could be a useful model to inform NLMT's Phone Support Service.…”
Section: Service Outlinementioning
confidence: 85%
“…Cette étude nous permettrad 'identifier la technique la plus efficace entre l'hypnose, la réalité virtuelle et l'hypnose en réalité virtuelled ans ce contexte de soin et de l'intégrer à une seconde étude dont l'objectif est d'améliorer la prise en charge des patients qui subissent un passage prolongé aux USI, sous ventilation mécanique. Il est reconnu que le passage aux USI représente pour les patients une agression qui peut s'accompagner d'un syndrome confusionnel aigu (ou délirium), d'anxiété et d'un syndrome de stress post-traumatique [8,9]. Quelques études proposent l'utilisation de techniques non-pharmacologiques comme la musicothérapie, les massages, l'acupuncture et la réflexologie afin de réduire le stress au quotidien et durant les procéduresmédicales [10,11].…”
unclassified